Milk quality characteristics from Greek indigenous goats - SKOUFOS, I.; TZORA, A.; KARAMOUTSIOS, A.; TSANGARIS, G.; GIANNENAS, I.; FTHENAKIS, G. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
The aim of this study was to assess the chemical and microbiological characteristics of goat milk from indigenous Greek breeds, domestic (Capra prisca) and Skopelos. Εach breed’s milk yield was recorded three times during lactation (early, mid and late stage of lactation) for two consecutive years. No significant differences were observed for fat, protein, lactose, casein and solids-non-fat contents of milk from both breeds. The dominant fatty acids (FA) in milk for both breeds were: palmitic (C16:0) and oleic (C18:1). Other abundant FA was stearic (C18:0), myristic (C14:0), capric (C10:0) and lauric (C12:0). The conjugated linoleic acid (CLA) content was similar in both breeds. Linolenic acid content in milk of Capra prisca breed was higher than in Skopelos.A high number of minor short chain fatty acids (SCFA), medium chain fatty acids (MCFA) and long chain fatty acids (LCFA) was also observed in milk fat. SCFA’s increased in mid lactation in goats of Capra prisca breed, while no significant differences were noted during early, mid or late lactation period in medium or long chain FA. In Skopelos breed, SCFA’s increased gradually from early to late lactation, while LCFAs followed a descending order. Enumeration of bacteria presented similar numbers of total viable count in milk of both breeds and higher number of Psychrotrophic ones in milk from Skopelos goats to domestic. Somatic cell counts (SCC) values were significant lower in Skopelos breed compared to Capra prisca. Caprine milk can be an important sourceof health promoting substances and deserves further investigation with specific investigation on milk of indigenous local breeds.